La loi du 3 janvier 1979 (France) et la communication des documents - Charpy, Jacques (La Gazette des archives, 1979)

La loi du 17 juillet 1978 (France) : de la liberté d'accès aux documents administratifs - Gorgeon-Demartres, A. (La Gazette des archives, 1979)

Les généalogistes et les Archives - Wolff, Christian (Gazette des archives, 1979)
Genealogists and archives. Difficultes encountered and examples of solutions adopted by several archive institutions to meet the increasing number of genealogists. The growing importance of this category of researchers and the risks which they inflict on the preservation of documents make it advisable that archivists adopt a common attitude in their relations with genealogists. Better organisation and discipline of genealogists themselves would make these relations easier.